Функціонально-дискретний метод розв'язування задач на власні значення для нелінійних диференціальних рівнянь - Макаров, В.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
A new functional-discrete method to solve eigenvalue problems for ordinary differential operators of the Schr¨odinger type with nonlinear potentials is proposed. The method approximates both eigenvalues and eigenfunctions superexponentially. The efficiency of the method is illustrated by several numerical experiments.